PENGEMBANGAN MODEL SUPERVISI KEPALA SEKOLAH BERBASIS BAGJA (BUAT AGENDA, AMBIL PELAJARAN, GALI MIMPI, JABARKAN RENCANA, ATUR EKSEKUSI) UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU SEKOLAH DASAR DI KECAMATAN ULUJAMI KABUPATEN PEMALANG - Riningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low level of pedagogical competence among elementary school teachers in Ulujami Subdistrict, Pemalang Regency, has become a serious concern in efforts to improve education quality. This study aims to develop a school principal supervision model based on the BAGJA approach to enhance pedagogical competence. Using the R&D method adapted from Borg and Gall, the study involves stages of preliminary research, model development, and validation. The research indicates that the BAGJA-based supervision model is practical, effective, and applicable to real school conditions. This model enables principals to provide structured, solution-oriented supervision, helping teachers to improve planning, implementation, and evaluation of learning.